Is citizen journalism is similar to keyboard warriors and cyber troopers? an exploration and meanings from citizen journalists’ experience - Mahamed, Mastura; Omar, Siti Zobidah; Krauss, Steven Eric (Human Resource Management Academic Research Society, 2020)
Citizen journalism has the reputation being generalized as having a negative affiliation more than its potentials. Many attributed citizen journalism with skepticism and cynical phenomenon. This qualitative study is conducted to find out if youth citizen journalists have the same philosophy and view about the phenomenon and if they associate themselves with keyboard warriors and cyber troopers as well as the ethical aspects of journalism practices applied among youth citizen journalists in Malaysia. Nine informants from various states in Malaysia participated in the phenomenological study. The research question as to ways they separate themselves from keyboard warriors and cyber troopers in citizen journalism landscape in Malaysia Findings based on the themes emerged suggested that they highlighted the differences between them and keyboard warriors as well as cyber troopers, the challenges they faced as citizen journalists facing keyboard warriors and cyber troopers.